The new weird - VanderMeer, Ann ca. 20./21. Jh; VanderMeer, Jeff 1968- (Tachyon Publications, 2008)
Presents a collection of stories from the "new weird" genre...a overlap of science fiction, fantasy, and horror...from some of its well-known writers, along with commentaries and a story featuring emerging authors within the genre